Strategi Metode Student Facilitator and Explaining dalam Meningkatkan Prestasi Belajar Peserta Didik - Nor Mubin (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2019)
Learning by Student Facilitator And Explaining Method influences the learning achievement of students. Student Facilitator And Explaining is a series of learning activities beginning with teacher delivering the material by demonstration, then students are given opportunity to explain back to other students using other forms, such as charts, maps or concepts. Implementation of learning with this technique invites students to participate actively in learning. Students observe the material through demonstration. Students note important things that are demonstrated by the teacher, make conclusions. Furthermore, students also make a chart of the teacher's explanation as material to explain back to other students. The learning process with this technique students can increase activity, motivation, and creative thinking that makes learning more interesting and enjoyable. Students are not only as learning objects, but also as subjects who understand concepts through observation, discovering, and constructing the concepts owned by students with newly acquired concepts so that their learning achievement increases. Learning achievement achieved by someone is the result of interaction various factors that influence both internal and environmental factors.